Pengaruh Kualitas Pelayanan terhadap Minat Beli Ulang dengan Kepuasan Konsumen sebagai Variabel Intervening - Sulastini, Ni Wayan; Adisti Abiyoga Wulandari, Ni Luh; Indra Surya Diputra, Gde (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the effect of service quality on customer satisfaction, to determine the effect of service quality and customer satisfaction partially on repurchase intention and to determine the indirect effect of service quality on repurchase intention through customer satisfaction. The location of this research is the customer at Tarukan Photo Studio in Denpasar. The sample in the research is 98 respondents. The research method used is quantitative. The data analysis technique used in this study is the validity test, reliability test, and sobel test. From the results of the study it can be seen that service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on repurchase intention, customer satisfaction has a positive and significant effect on repurchase intention, and service quality has an indirect effect on repurchase intention through consumer satisfaction. Suggestions that can be given by researchers are that Tarukan Photo Studio in Denpasar is expected to improve the quality of services provided, by providing training to employees and supervising employees in providing services so that employees are able to provide fast, precise and responsive responses to customers